Nonenzymatic Detection of Glucose Using 3D Printed Carbon Electrodes in Human Saliva - Dalton L. Glasco; Manar M. Elhassan; William T. McLeod; Jeffrey G. Bell (ECS Sensors Plus, 2024)
One of the most prevalent diseases where point-of-care (POC) diagnostics has focused is diabetes, which impacts hundreds of millions of people globally. Due to the severe negative outcomes including renal failure, nerve damage, and stroke, many POC sensors have been designed to streamline low-cost testing. Recently, the utility of 3D printing for rapidly fabricating housings, electrodes, and sensors for use at the POC has been exploited toward diverse applications. Particularly interesting are 3D printed carbon electrodes (3DpCEs) in POC diagnostics owing to their simplicity, affordability, and mass production capabilities for developing sensors either for direct use or through post-printing surface modifications. Herein, we report a copper modified 3DpCE as a sensitive and selective nonenzymatic biosensor for glucose. Copper deposition, paired with an optimized activation protocol, produced a sensitive and selective sensor for glucose with a larger detection range, enhanced sensitivity, and better reproducibility compared to nonactivated and alkaline immersed 3DpCEs. The sensor displayed excellent linearity between 10–1800 μ M and proved to be highly selective over common biologically relevant interferants. The 3D printed sensor successfully determined biologically relevant concentrations of glucose in human saliva which resulted in percent recoveries of 101 ± 8%, 106 ± 6%, and 98 ± 6% for 74, 402, and 652 μ M glucose, respectively.